ALIH KODE DALAM DIALOG NOVEL SURGA YANG TAK DIRINDUKAN KARYA ASMA NADIA - Wulandari, Rina; Marmanto, Sri; Sumarlam, Sumarlam (Universitas Sebelas Maret, 2016)
The objectives of this research are to explain: (1) the forms of code switching in a dialogue of novel Surga yang Tak Dirindukan, (2) the factors influencing of code switching in a dialogue of novel Surga yang Tak Dirindukan, (3) the functions of code switching in a dialogue of novel Surga yang Tak Dirindukan. The research employed a Poplack’s sociolinguistics approach. The research using qualitative descriptive method. The data obtained from the dialogue of novel, then were analyzed by using the communicative ethnographic approach by considering the existing speech context, namely: speech components. The data of the research included speech dialogue in a novel there were code switching. The data collection of the research began by determining of novel, documentation technique, classification technique, and coding of data technique. Then, using ethnographic method with domain analysis technique, taxonomic analysis technique, componential analysis technique, and cultural of themes analysis technique. The data were validated using the triangulation technique and analyzed by means of the Spradley model of analysis. The result of the research shows that the forms of code switching are tag switching, intra-sentential code switching, and inter-sentential code switching through the use of declarative, imperative, and interrogative sentences. Tag switching consists of 24 data, intra-sentential code switching consists of 12 data, and inter-sentential consists of 49 data. The factors influencing the code switching in a dialogue of novel include to quoting others’ speech and being disposed for adjusting the language used with interlocutor. Finally, the functions of the code switching are to establish a good communication and to confirm the addressors’ speech. The conclusion of the research is inter sentential code switching most often appears with a percentage 57,6%, then tag switching is 28,2%, and the last is intra sentential code switching 14,1%. The factors influencing the code switching most often appears is Ends factor in a inter sentential code switching with percentage 24,7% and rarely appears is a act sequence factors in a tag switching with percentage 2,3%. And the last the functions of code switching most often appears to convince the hearer functions in a inter sentential code switching with percentage 12,9%, then never appears to respect hearer functions and to change situation or humor functions in a inter sentential code switching 0% Keywords: code switching, sociolinguistic study, Poplack’s sociolinguistics approach, Surga yang Tak Dirindukan